The Analysis of Transfusion Transmitted Infections (TTIs) in Thalassemia Patients - Batool, Tayyaba; Nawab, Shaheena; Mehmood, Badar; Younas, Nadeem Shahid; Khan, Muhammad Irfan; Nadeem, Khadija (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To find out the analysis of transfusion transmitted infections (TTIs) in β-thalassemia patients at a tertiary care hospital of South Punjab, Pakistan. Study Design: A cross-sectional study. Place and Duration of the Study: The Department of Hematological Disorder, Thalassemia and Bone Marrow Transplantation Centre, and Department of Biochemistry, “Bahawal Victoria Hospital, Quaid e Azam Medical College”, Bahawalpur, Pakistan from February January 2020 to December 2021. Methodology: Patients of blood transfusion-dependent ????-thalassaemia of both genders and aged 5 to 12 years were analyzed. Blood was collected from patients aseptically and serum separated in Eppendorf tubes and stored at –200C. Screening for hepatitis C virus (HCV), hepatitis B virus (HBV), syphilis and human immunodeficiency virus (HIV) were performed through Chemiluminescence Immunoassay (CLIA) technique. Results: In a total of 1212 patients, 745 (61.5%) were male. Overall, mean age was calculated to be 8.7±4.6 years while 874 (72.1%) patients were below 10 years of age. There were 866 (71.5%) patients who belonged to rural areas of residence. Parental consanguineous marriages were reported in 951 (78.5%) cases. There were 205 (16.9%) patients who were found to have TTIs. Out of these 205 patients, 169 (13.9%) were having HCV, 11 (0.9%) HBV, 20 (1.7%) syphilis whereas HIV was noted in 5 (0.4%) patients. Conclusion: Prevalence of TTIs was found to be high among multi-transfused patients of β-thalassemia. Most common types of TTIs were HCV which is consistent to what has previously been reported in the local literature. Identification of HIV in 0.5% cases in the present study is pointing towards disturbing development regarding spread of HIV in our region.